Does urban extent from satellite images relate to symptoms of asthma, rhinoconjunctivitis and eczema in children? A cross-sectional study from ISAAC Phase Three. (13th September 2016) - Pacheco-González, Rosa; Ellwood, Eamon; Exeter, Daniel; Stewart, Alistair W.; Asher, Innes; ,
Abstract: Objective : The relationship between urbanisation and the symptom prevalence of asthma, rhinoconjunctivitis and eczema is not clear, and varying definitions of urban extent have been used. Furthermore, a global analysis has not been undertaken. This study aimed to determine whether the symptom prevalence of asthma, rhinoconjunctivitis and eczema in centres involved in the International Study of Asthma and Allergies in Childhood (ISAAC) were higher in urban than rural centres, using a definition of urban extent as land cover from satellite data. Methods : A global map of urban extent from satellite images (MOD500 map) was used to define the urban extent criterion. Maps from the ISAAC centres were digitised and merged with the MOD500 map to describe the urban percentage of each centre. We investigated the association between the symptom prevalence of asthma, rhinoconjunctivitis and eczema and the percentage of urban extent by centre. Results : A weak negative relationship was found between the percentage of urban extent of each ISAAC centre and current wheeze in the 13–14-year age group. This association was not statistically significant after adjusting for region of the world and gross national income. No other relationship was found between urban extent and symptoms of asthma, rhinoconjunctivitis and eczema. Conclusions : In this study, the prevalence of symptoms of asthma, rhinoconjunctivitis and eczema in children were not associated with urbanisation, according to the land cover definition of urban extent from satellite data. Comparable standardised definitions of urbanisation need to be developed so that global comparisons can be made.